C++ Data Structures and Algorithms - Wisnu Anggoro (Packt Publishing, 2018)
This book, 'C++ Data Structures and Algorithms,' is your guide to mastering the implementation of essential data structures and algorithms in C++. Through practical examples, you'll develop the skills to build robust and scalable applications, enhancing your programming expertise.What this Book will help me doMaster the usage of arrays, stacks, trees, lists, and graphs through hands-on examples.Learn and implement efficient sorting techniques like heap sort, quicksort, and merge sort.Understand and apply searching methodologies including linear, binary, and advanced search algorithms.Gain proficiency in designing algorithms tailored for optimization and performance.Develop the ability to analyze, debug, and optimize data structures and algorithms for real-world applications.Author(s)Wisnu Anggoro is a seasoned software developer with deep expertise in C++ programming and a passion for teaching technical concepts. Having authored works in programming, Wisnu aims to break down complex ideas into accessible knowledge. His approach combines practical examples with theoretical foundations.Who is it for?This book is ideal for aspiring C++ developers looking to deepen their understanding of data structures and algorithms. If you have foundational knowledge in C++ and want to enhance your skills in creating efficient and scalable software solutions, this is the book for you. Both students and professionals venturing into advanced programming will find this a valuable companion. No matter whether you're looking to sharpen your skills for job preparedness or personal growth, this guide has you covered.